2018
DOI: 10.1155/2018/1462802
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Induced Rodent Model of Kidney Injury: Characteristics and Challenges

Abstract: Cisplatin is an antitumor drug used in the treatment of a wide variety of malignancies. However, its primary dose-limiting side effect is kidney injury, which is a major clinical concern. To help understand mechanisms involved in the development of kidney injury, cisplatin rodent model has been developed. Given the complex pathogenesis of kidney injury, which involves both local events in the kidney and interconnected and interdependent systemic effects in the body, cisplatin rodent model is indispensable in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
140
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(172 citation statements)
references
References 189 publications
(220 reference statements)
7
140
1
4
Order By: Relevance
“…clinical markers for renal tissue injury, including the levels of serum Bun and Scr, were investigated to evaluate cP-induced nephrotoxicity. it has previously been reported that a single dose of cP (3-8 mg/kg) can cause acute nephrotoxicity and induce changes to kidney structure and function in rats (32). in the present study, animal models of cP-induced aKi were established by i.p.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…clinical markers for renal tissue injury, including the levels of serum Bun and Scr, were investigated to evaluate cP-induced nephrotoxicity. it has previously been reported that a single dose of cP (3-8 mg/kg) can cause acute nephrotoxicity and induce changes to kidney structure and function in rats (32). in the present study, animal models of cP-induced aKi were established by i.p.…”
Section: Resultsmentioning
confidence: 78%
“…Dex treatment ameliorates CP-induced apoptosis of tubular epithelial cells. apoptotic cell death is the major pathological process which renal tissue undergoes as a result of cP toxicity (32). To investigate whether dex protected renal tubular epithelial cells against apoptosis induced by cP, tubular cell apoptosis was detected in the present cP-induced aKi model using Tunel assay.…”
Section: Resultsmentioning
confidence: 97%
“…Despite intense prophylactic attempts, nephrotoxicity has been reported even in 20%-30% of patients who received a single dose of cisplatin [1]. As renal toxicity is accepted to be cumulative, it is suggested that successive use of cisplatin would increase the incidence and severity of toxicity [6].…”
mentioning
confidence: 99%
“…Cisplatin is known to demonstrate toxic effects on the renal tubule, vasculature, and glomeruli. It results in structural damage to the kidney and consequently increases creatinine and urea in blood [37][38][39]. Panaxynol treatment reduced the serum creatinine and BUN in mice with cisplatin-induced kidney injury.…”
Section: Discussionmentioning
confidence: 99%